Cardiovascular Disease Multimorbidity and Decreased Health‐Related Quality of Life in Haiti: A Cross‐Sectional Study - Shalom Sabwa; Vanessa Rouzier; Rodney Sufra; Reichling St. Sauveur; Nour Mourra; Rehana Rasul; Joseph Inddy; Lily D. Yan; Madeline Sterling; Laura Pinheiro; Marie Deschamps; Jean William Pape; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Multimorbidity is increasingly prevalent in lower‐ and middle‐income countries. Health‐related quality of life (HRQOL) has been inversely associated with multimorbidity but is understudied in lower‐ and middle‐income countries. We report cardiovascular disease (CVD) multimorbidity in Haiti and its association with HRQOL. Methods and Results We used data from the Haiti CVD Cohort, a population‐based longitudinal cohort of adults. CVD multimorbidity was 2+ CVD risk factors/diseases at enrollment. HRQOL was measured using the Short Form‐12, yielding physical component summary/mental component summary scores between 0 and 100, with higher scores indicating better HRQOL. We used linear regressions to assess the association between CVD multimorbidity and HRQOL and individual CVD comorbidities and HRQOL. Additionally, we examined sex and education as potential effect modifiers. Among 2,996 participants, the median age was 40 years (interquartile range [IQR], 27–55), 58.0% were women, and 70.3% earned <1 US dollar per day. CVD multimorbidity prevalence was 24.1%; compared with those without CVD multimorbidity, those with CVD multimorbidity were older (median age, 56.0 years [IQR, 47.0–53.0]) and women (70.5%). Adjusted models revealed CVD multimorbidity was inversely related to physical component summary (−2.7 [95% CI, −3.8 to −1.6]) and mental component summary (−1.0 [95% CI, −1.8 to −0.2]). Heart failure and hypertension showed the strongest CVD morbidities associated with poor HRQOL. In the interaction analysis, among men, CVD multimorbidity was associated with a 4.3‐point lower physical component summary score. Among those with less education, CVD multimorbidity was associated with a 4.6‐point lower physical component summary score than no CVD multimorbidity. Conclusions Our data are among the first to describe HRQOL data with high CVD multimorbidity in a young population in urban Haiti, and CVD multimorbidity was associated with decreased HRQOL. Registration URL: https://www.clinicaltrials.gov; Unique identifier: NCT03892265.